2017
DOI: 10.1080/15384101.2017.1295186
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses identify molecular signature of MRI-classified SVZ-associated glioblastoma

Abstract: Glioblastoma (GBM) is a highly aggressive brain cancer with limited therapeutic options. While efforts to identify genes responsible for GBM have revealed mutations and aberrant gene expression associated with distinct types of GBM, patients with GBM are often diagnosed and classified based on MRI features. Therefore, we seek to identify molecular representatives in parallel with MRI classification for group I and group II primary GBM associated with the subventricular zone (SVZ). As group I and II GBM contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“… Qin et al (2017) reported that precursor neuronal cells of the ependymal region may attract tumor cells to migrate to the ventricle, but he did not mention whether the GBM penetrated into the ventricle. Another study suggested that GBM located in proximity to the ependymal region exhibited mRNA expression profiles associated with stem cell properties and increased DNA repair capacity, and that might be associated with GBM-ependymal contact ( Lin et al, 2017 ; Steed et al, 2020 ). However, Akshitkumar et al reported that after excluding the volume factor of the sample, there was no significant difference in gene expression between GBM with and without contact with the ependymal region.…”
Section: Discussionmentioning
confidence: 99%
“… Qin et al (2017) reported that precursor neuronal cells of the ependymal region may attract tumor cells to migrate to the ventricle, but he did not mention whether the GBM penetrated into the ventricle. Another study suggested that GBM located in proximity to the ependymal region exhibited mRNA expression profiles associated with stem cell properties and increased DNA repair capacity, and that might be associated with GBM-ependymal contact ( Lin et al, 2017 ; Steed et al, 2020 ). However, Akshitkumar et al reported that after excluding the volume factor of the sample, there was no significant difference in gene expression between GBM with and without contact with the ependymal region.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have sought to understand the molecular basis for the increased malignancy of glioblastomas with VSVZ contact (17)(18)(19). Two of them demonstrate a correlation with increased glioblastoma expression of CD133, a glioma stem cell marker, with proximity to the VSVZ (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…These molecular approaches to GBMs revolutionized the understanding of the pathophysiology of gliomas, pathologic classification of tumors, and therapeutic approaches, even if all these genetic classifications do not routinely influence treatment choices. 79 It is possible that further GBM subclassifications will lead toward individualized treatments for distinct molecular subtypes. GBM patient samples taken during the first tumor resection and after first-line chemotherapy, done during second tumor resection for recurrent GBMs, can be useful to understand the changes occurring in gene and protein expression, to improve pharmacologic research, and to establish the most effective pharmacotherapy for the single patient.…”
Section: Discussionmentioning
confidence: 99%